Using PLS-SEM and Interpretative Analysis for Testing Questionnaire of The Success of Information Systems Strategic Planning Benefit Realization. - Bernadus, Gunawan Sudarsono; Aedah, Abd Rahman; Manorang, Sihotang; Alexius, Ulan Bani; Agus, Budiyantara; Rouly, Doharma (2012)
The purpose of this study was to examine the ISSP (Information System Strategic Planning) questionnaire which was related to the factors that influence the success of ISSP, namely in terms of the realization of benefits, with the college population as an example of data collection. This test was carried out using PLS-SEM and interpretative analysis. PLS-SEM analysis is used to test the validity and reliability statistically of the 41 questions in the questionnaire. These statistical results are then used in interpretive analysis which will produce a justification to be taken into consideration in the better updating of the questionnaire. The results of these two analyzes have identified that 3 of the 41 questions recommended are omitted. The benefits of this study are input for other researchers in practical and methodological terms.